Electronic nose system for rancidity and insect monitoring of brown rice - Natawut Neamsorn (2020)
© The Authors, published by EDP Sciences, 2020. Electronic nose system was designed and fabricated for classification of rancidity and pest damages in brown rice. The electronic nose system was included gas handling system, sensors array and data acquisition and processing system. Response signal from sensors array was recorded and processed. The results showed that the E-nose could classify normal and rancid brown rice (KDML105) and the classification model had Rv2 = 0.92 and SEP = 0.14. The model also gave satisfactory result for classification of brown rice which was damaged by insects (Tribolium castaneum) with Rv2 =0.98 and SEP = 0.06. It was possible to use electronic nose as the quality monitoring system during storage of KDML105 brown rice.